Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5539/jas.v12n8p92
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compound Based Markers for the Aroma Trait of Rice Grain

Abstract: A study was conducted to determine the volatile organic compounds (VOCs) associated with rice grain aroma in 37 commonly grown lines within Uganda, as well as elites. The aim of the study was to identify potential volatile biochemical markers, if any, for the rice grain aroma trait. Certified rice seeds were obtained from the Uganda National Crops Resources Research Institute germplasm collection. The seeds were sown into experimental plots, under field conditions and the mature paddy harvested. Polished rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…VOCs are often derived from alanine, valine, leucine, isoleucine, and methionine (Knudsen et al, 2006 ). We only identified one amino acid derivative in soybean, O-Decyl Hydroxylamine (CPV34), an N-containing compound, which has not been well studied, but has been shown to be expressed in certain rice grains (Ocan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…VOCs are often derived from alanine, valine, leucine, isoleucine, and methionine (Knudsen et al, 2006 ). We only identified one amino acid derivative in soybean, O-Decyl Hydroxylamine (CPV34), an N-containing compound, which has not been well studied, but has been shown to be expressed in certain rice grains (Ocan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 2AP has been considered the key compound influencing aroma in rice [5]. Ocan et al [33] recently found 41 VOCs to be significantly correlated with 2AP in 37 lines that are commonly grown in Uganda.…”
Section: Molecular and Genetic Bases Of Rice Aromamentioning
confidence: 99%
“…These methods include sensory evaluation, electronic nose, near-infrared spectroscopy and gas chromatography methods [5]. Aroma strength can be analysed using gas chromatography, which is used to assess the amount of 2AP content in rice leaves and grains [18,33]. Aroma can be smelt after soaking rice grains in KOH solution [33,36,47].…”
Section: Breeding For Aroma In Ricementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the relation with flavoring properties and VOCs-based markers for the rice aroma traits, the emerging role of volatile compounds and their precursors of plant foods, such as health benefits and reliable indicators of quality modifications and cellular biochemical reactions, has been recently highlighted (Ayseli & Ayseli, 2016;Ocan et al, 2020;Xia et al, 2020b;Xia et al, 2022). In this work, the volatile fingerprinting was monitored to clarify the ultrasonic effects on the quality-related chemical reactions, particularly the possible synergistic and/or antagonistic effects induced by combined physical fields via identifying the most quality relevant VOCs metabolites as influenced by hpu irradiation pretreatments during storage process.…”
Section: Volatile Fingerprinting Identified By Untargeted Headspace G...mentioning
confidence: 99%